On the robustness of spider capture silk's adhesion. (May 2019) - Guo, Yang; Zhao, Hong-Ping; Feng, Xi-Qiao; Gao, Huajian
Abstract: Through evolution, spider orb webs have acquired an outstanding ability to capture flying preys. In this work, we aim to understand the robustness of spider adhesion by analyzing the effects of randomness in the adhesion strengths and inter-spacings of glue droplets along a spider orb web capture silk on its load-bearing and energy absorption capacities when adhered on a substrate. It is found that the spider silk exhibits a high level of robustness in the sense that both its total adhesion strength and energy absorption capacity are insensitive to random mechanical and geometric imperfections. Specifically, randomness in the spatial distributions of glue droplets is shown not to deteriorate the adhesion property, rather it can slightly enhance the load-bearing and energy absorption capacities of the silk. This finding may help us understand the principle of spider adhesion and guide the design of spider-inspired adhesion and capture devices.